Moluccas Local Wisdom in the Role of Marriage Arbitrator for Preventing Domestic Violence - Ahmad Lonthor; La Jamaa (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2020)
This research aims to reveal the Moluccas local wisdom through the existence of marriage arbitrators among Muslim community in Salahutu, Leihitu, and West Leihitu, Central Maluku. The data were collected through observation and interviews with community leaders, marriage arbitrators and their married sisters and then analyzed descriptively and qualitatively. The research results showed that the marriage arbitrators come from a male distant relative who was appointed by custom as a part of the marriage custom. The appointment aims to strengthen the family relationship between the bride (married sister) and the arbitrator in which they can help each other. Traditionally, an arbitrator serves to help the bride in both material and non-material aspects, particularly in preventing domestic violence. He can become a mediator, peacemaker, and helper of the economic hardship as well as preventing the married sister from psychological domestic violence. Furthermore, he can also provide protection for his married sister from the threat of her husband’s physical violence. This research found that the role of marriage arbitrators as peacemakers in preventing husband’s violence against their married sisters is relevant to hakamain concept in Islamic law as well as the provisions of "safe houses by the community," in Law No. 23/2004.(Tulisan ini bertujuan untuk mengungkapkan peran kearifan lokal saudara kawin  pada masyarakat Muslim di Kecamatan Salahutu, Leihitu dan Leihitu Barat Kabupaten Maluku Tengah. Data dikumpulkan melalui observasi dan wawancara kepada tokoh masyarakat, saudara kawin dan saudari kawin kemudian dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa saudara kawin adalah laki-laki dari kerabat jauh yang diangkat secara adat sebagai bagian dari adat perkawinan. Hal itu bertujuan untuk mempererat hubungan kekeluargaan antara saudara kawin dengan saudari kawinnya di mana keduanya bias saling membantu. Secara adat, saudara kawin bertugas membantu mempelai perempuan (istri) dalam hal material maupun non-material, utamanya untuk mencegah tindak kekerasan dalam rumah tangga si saudari kawin. Saudara kawin bisa berperan sebagai penengah, juru damai, sekaligus membantu kesulitan ekonomi keluarga saudari kawinnya, termasuk mencegah terjadinya kekerasan psikis saudari kawinnya. Lebih jauh, saudara kawin juga bisa berperan melindungi saudari kawinnya dari ancaman kekerasan fisik suaminya. Temuan penelitian ini menunjukkan bahwa peran saudara kawin sebagai juru damai yang mencegah kekerasan suami kepada istri relevan dengan konsep hakamain dalam hukum Islam serta ketentuan ”rumah aman oleh masyarakat,” dalam Undang-undang RI Nomor 23 Tahun 2004)